Computational thinking in problem solving contextualized in a story in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
Over the last years, educational computering and robotics have become a reality in the classroom context. Computational thinking has become a subject worth of study, mainly due to the growing number of papers around its introduction in Early Years Education. In Infant Education, the development of computational thinking contributes to the student ́s cognitive development and fosters the learning skills. This present research project is based on the resolution of a sequence of mathematical problems set in a context familiar to Infant Education students, which is close to their interests and motivation. By means of a floor robot with advanced remote control, Next 1.0., it is intended to initiate the students in the language of robotics and computational thinking. Through affectivity, experiences which motivate students to search for solutions to the approaches proposed it is intended to be generated.
Keywords: Computational thinking; Educational robotics; Resolution of mathematical problems; Spatial orientation; Flow experiences